2012
DOI: 10.3839/jabc.2011.052
|View full text |Cite
|
Sign up to set email alerts
|

The Antifungal Activity of Bee Venom against Dermatophytes

Abstract: The antifungal activities of the bee venom against Trichophyton mentagrophytes and Trichophyton rubrum were determined by using modified broth dilution assay. The most common dermatophytes, named T. mentagrophytes and T. rubrum, were known to cause a variety of cutaneous infections in humans and animals. The bee venom exhibited prominent antifungal activities against the two dermatophytes tested in this investigation. Moreover, the antifungal activities of the bee venom were much stronger than that of fluconaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…1 ). However, Yu et al [ 38 ] reported that the antifungal activities of BV against Trichophyton mentagrophytes and Trichophyton rubrum were much stronger than those of fluconazole, one of the commercial antifungal drugs that is currently being used. In the current study, amphotericin B was used as a positive control: amphotericin B is a fungicidal agent that is widely used to treat serious systemic infections [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 ). However, Yu et al [ 38 ] reported that the antifungal activities of BV against Trichophyton mentagrophytes and Trichophyton rubrum were much stronger than those of fluconazole, one of the commercial antifungal drugs that is currently being used. In the current study, amphotericin B was used as a positive control: amphotericin B is a fungicidal agent that is widely used to treat serious systemic infections [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…BV or its series of components have shown a broad array of effects from anti-inflammatory agents, anti-nociceptive, antibacterial, to anti-tumorous effects 1 2 3 4 5 6 7 8 . Extensive in vitro studies have confirmed the versatile properties that BV retains.…”
Section: Discussionmentioning
confidence: 99%
“…One theory is that while mellitin induces reactive oxygen species to generate the antifungal effect, other components such as phospholipase A2, hyaluronidase which respectively raise the permeation of the cell membrane and the capillary membranes are necessary to give the whole antifungal effect 1 13 14 22 23 . Additionally, studies state that the lipids and carbohydrates in the venom may act as an opsonin for further inflammatory responses to repeatedly generate the antifungal effect 22 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations